Modelling early childhood teachers’ mathematics-specific professional competence and its differential growth through professional development–an aspect of structural validity - Lindmeier, Anke; Seemann, Selma; Kuratli-Geeler, Susanne; Wullschleger, Andrea; Dunekacke, Simone; Leuchter, Miriam; Vogt, Franziska; Opitz, Elisabeth Moser; Heinze, Aiso (Research in Mathematics Education, 2020)
Research on teacher knowledge has been criticised for taking too narrow a view on expertise. Therefore, teacher competence frameworks have been developed that are closely related to professional demands. Their practice-oriented conceptualisations have led to innovative measures with situative demands. However, there is still a lack of knowledge on whether these frameworks are actually suited to map teacher growth. This study investigated whether two components of teacher competence, Action-related (AC) and Reflective Competence (RC), can be differentially fostered through specific interventions in early childhood mathematics education. We designed two professional development programmes with a focus on AC and RC and implemented them in a randomised controlled experiment with 170 teachers. Overall, we found that AC, RC, and professional knowledge were sensitive to interventions with different change profiles. Although our hypotheses were only partially supported, the results can be seen as evidence regarding the distinctness of competence and knowledge components.
CRIS-Team Scopus Importer:2024-10-02
Keywords: early mathematics; experimental study; Teacher competence